1987
DOI: 10.1111/j.1399-0039.1987.tb01567.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA and leprosy in Koreans

Abstract: HLA antigens in 157 unrelated Koreans with leprosy have been identified and compared with 162 healthy Korean controls. The patient group consisted of 124 with lepromatous leprosy and 33 with tuberculoid leprosy. Although no significant differences were detected between the two patient groups, several antigens were found to be increased in the combined patient group compared to healthy controls. Two Class I antigens were increased: HLA-All (22% vs 12%) and Aw33 (27% vs 14%). Four Class I1 antigens were increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Table 4 summarizes results obtained from other HLA-A, -B, and -DRB1 disease association studies in other populations [6 -15,25,26]. Although there is some discordance between studies, the same protective association with HLA-DRB1‫/5040ء‬DR4 and leprosy was also observed in three studies [7,8,14].…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Table 4 summarizes results obtained from other HLA-A, -B, and -DRB1 disease association studies in other populations [6 -15,25,26]. Although there is some discordance between studies, the same protective association with HLA-DRB1‫/5040ء‬DR4 and leprosy was also observed in three studies [7,8,14].…”
Section: Resultsmentioning
confidence: 50%
“…Furthermore Joko et al previously reported that the presence of HLA-DRB1‫5040ء‬ was significantly decreased in Japanese leprosy patients (OR ϭ 0.25) and that the multibacillary group had less DRB1‫5040ء‬ than paucibacillary group [7]. In addition, Kim et al and Vanderborght et al also reported that DR4/DRB1‫40ء‬ was associated with resistance to M. leprae infection in Korean, Vietnamese, and Brazilian populations [8,14] (Table 4). Although association analyses in these studies were obtained using HLA-DR serology (i.e., using two-digit resolution typing), our study, using re-assignation NS, not significant.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[143][144][145][146][147] DRB1*1501 has been associated with LL 148,149 whereas DRB1*1502 has been associated with TT. 150 DQ alleles, especially DQw1 have been shown to be associated with TT in India, 148,123 Korea, 141 Thailand, 149 and Japan. 151 Importantly, HLA DQ1 is in strong linkage disequilibrium with HLA-DR2 in most populations and it has usually been difficult to discern whether the primary association is with the DR or the DQ variant.…”
Section: -133mentioning
confidence: 99%
“…136 Several studies comparing HLA Class I gene frequencies in leprosy cases and controls have found associations either with the polar forms of leprosy, or with leprosy itself, however these suggested associations have not been replicated as they are limited and inconsistent. 130,[137][138][139][140][141][142] The association between DR and DQ alleles and different clinical subtypes of leprosy are documented. Several studies reported an association of the HLA-DR2 alleles; HLA -DRB1*15, *16, *10 and *12 with susceptibility or resistance to leprosy in Brazilian, Vietnamese, South Indian, Indonesian, Thai and Argentine populations.…”
Section: -133mentioning
confidence: 99%